Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/8769360
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Hydrophobic Modification of Cotton Stalk Bark Fiber

Abstract: Cotton stalk bark fiber (CSBF) was extracted at high temperature and under high pressure, under the condition of the alkali content of 11 wt%. Experimental results proved that the extraction yield of CSBF was 27.3 wt%, and the residual alkali concentration was 2.1 wt%. Then five kinds of modifiers including methyl methacrylate (MMA), MMA plus initiator, epoxy propane, copper ethanolamine, and silane coupling agent were chosen to modify the surface of CSBF. It was found by measuring water retention value (WRV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Moreover, it is reported that the cellulose fibers from cotton stalks have higher mechanical properties than those from most lignocellulosic byproducts. Many studies show that alkali treatment removes amorphous materials such as hemicellulose, lignin, and pectin from the surface of cellulose fiber bundles and develops interfacial bonding between fiber and matrix which provide better mechanical properties (Hou et al, 2014;Reddy and Yang, 2009;Sachan et al, 2017;Zhou et al, 2017;Li et al, 2016). In addition, it has been observed that with the increase in temperature, the amount of cellulose also increased.…”
Section: Thermal Assisted Alkaline Pretreatmentmentioning
confidence: 99%
“…Moreover, it is reported that the cellulose fibers from cotton stalks have higher mechanical properties than those from most lignocellulosic byproducts. Many studies show that alkali treatment removes amorphous materials such as hemicellulose, lignin, and pectin from the surface of cellulose fiber bundles and develops interfacial bonding between fiber and matrix which provide better mechanical properties (Hou et al, 2014;Reddy and Yang, 2009;Sachan et al, 2017;Zhou et al, 2017;Li et al, 2016). In addition, it has been observed that with the increase in temperature, the amount of cellulose also increased.…”
Section: Thermal Assisted Alkaline Pretreatmentmentioning
confidence: 99%